Apprenticing the jazz performer through ensemble collaboration: A qualitative enquiry. (May 2020) - de Bruin, Leon R; Williamson, Paul; Wilson, Emily
The one-to-one teacher–student relationship is a common learning configuration within jazz education. However, opportunities to learn through engagement in ensemble performances and industry-level recording opportunities with esteemed jazz performers are rare classroom environments the tertiary jazz music institutions offer. This qualitative study examines 'real-world' jazz performance contexts within an Australian tertiary music course, exploring students' learning experience spanning three diverse collaborative projects. Bandura's Social Cognition Theory is utilized to elucidate an ecological system of musical development, where learning occurs in a social context within dynamic, reciprocal interactions between learners, environment and students' adaptive behaviours that are bounded by context, culture and learner history. Findings from pre- and post-participation interviews reveal student and educator perspectives of engaging in authentic experiential learning situations. A stratum of positive influences impacting students included metacognitive, behavioural, emotional affordances, as well as the cultivation of a wider social, environmental and cultural/creative confidence and an expanding collaborative community influencing individuals' learning decisions. Students and educator participants expressed professional-level expectations, real-world outcomes, and a deeper musical connection and understanding by students of the guest artist/composers' intention, musical aesthetic and expert band direction. The authors maintain that inclusion of experience-based education and embedding of authentic professional industry experience and creative music-making contexts within educational settings enhance the learning of students and potentially enculturate richer musicianship in students and their developing creative communities.